Pola Ruang Bersama pada Permukiman Madura Medalungan di Dusun Baran Randugading - Indeswari, Ayu; Antariksa, Antariksa; Pangarsa, Galih Widjil; Wulandari, Lisa Dwi (RUAS, 2013)
In human social life, social space created. The kind of social space divided based on its characteristic. Communal space is a part of traditional Nusantara architecture that also means as social spac. It symbolized togetherness. In Madura community, tanean is communal space that has specific meaning. When they migrated to another land, they brought their dwelling tradition to the new land they have occupied. They called Madura Medalungan. One of the land occupied by Madura Medalungan is Baran Randugading, Malang. With the difference environment and culture setting, they adapt their communalspace with the new condition. The new models of communal space of Madura Medalungan society in Baran Randugading need to be studied. The result of the study showed that tanean, terrace or emper, front room or balai, traditional kitchen, langgar, and inter-space between house, were the most frequent used as communal space. In adition, mosque, village street, warung or shop, became communal space in accidental moment.Key words : Shared space, model, Madura Medalungan